Optimal Design and Economic Evaluation of Dividing‐Wall Columns. Issue 6 (15th March 2016) - Long, Hai; Clark, Jennifer; Benyounes, Hassiba; Shen, Weifeng; Dong, Lichun; Wei, Shun'an
Abstract: In an effort to reduce costs, a systematic optimization approach is proposed to address the energy consumption of dividing‐wall columns (DWCs). This iterative optimization procedure begins by minimizing the overall heat duty using an innovative objective function within a constrained design space. A sensitivity analysis is then carried out on the manipulated variables to obtain their optimal ranges. Optimal operating parameters are obtained through the evaluation of the total annualized cost (TAC). For the separation process of benzene/toluene/ o ‐xylene, the optimal DWC flow sheet exhibits a significant decrease in TAC when compared to conventional flow sheet optimum designs. The applied optimization method and sensitivity analysis have proven to produce results at the global optimum. This method is both practical and easily applied to other systems, even to systems with more than three components. Abstract : In order to reduce energy and capital costs, an innovative systematic optimization approach is proposed to address the energy consumption of dividing‐wall columns. The applied optimization method and sensitivity analysis provided results at the global optimum. This practical method can be easily applied to other systems, even to those with more than three components.